Апроксимація звичайних диференціальних операторів - Литвин, О.М. (Видавничий дім "Академперіодика" НАН України, 2007)
Basic statements of the theory of the approximation of ordinary differential operators by other ordinary differential operators are given. Approximating operators are not the equal on the given system of functions (functional knots).